Marie's magic eggs : how Marie Procai kept the Ukrainian art of pysanky alive - Wallace, Sandra Neil (Calkins Creek, an imprint of Astra Books for Young Readers, 2026)
As a new immigrant to America, Marie Procai felt homesick and alone -- she missed her homeland, Ukraine. She took comfort in the ancient Ukrainian art of making pysanky, intricately decorated eggs for Easter, an art she'd learned from her grandmother and brought with her to America. Cradling the pysanka in her hands felt like holding a piece of her homeland and giving her Baba a hug. Making pysanky made Marie feel a little more hopeful when the Russia's Red Army invaded Ukraine and forbade anyone from speaking Ukrainian or practicing their traditions, pysanky included. It sustained her spirit when her son was off fighting in World War II, and again when she welcomed Ukrainian refugees into her home after the war. A hardworking entrepreneur, Marie founded the Ukrainian Gift Shop in Minneapolis to keep Ukrainian culture alive in America and share it with everyone.